Preconceptional smoking alters spermatozoal miRNAs of murine fathers and affects offspring’s body weight - Hammer, Barbara; Kadalayil, Latha; Boateng, Eistine; Buschmann, Dominik; Rezwan, Faisal I.; Wolff, Martin; Reuter, Sebastian; Bartel, Sabine; Knudsen, Toril Mørkve; Svanes, Cecilie; Holloway, John W.; Krauss-Etschmann, Susanne (Nature Publishing Group, 2021)
Background Active smoking has been reported among 7% of teenagers worldwide, with ages ranging from 13 to 15 years. An epidemiological study suggested that preconceptional paternal smoking is associated with adolescent obesity in boys. We developed a murine adolescent smoking model before conception to investigate the paternal molecular causes of changes in offspring’s phenotype. Method Male and female C57BL/6J mice were exposed to increasing doses of mainstream cigarette smoke (CS) from onset of puberty for 6 weeks and mated with room air (RA) controls. Results Thirteen miRNAs were upregulated and 32 downregulated in the spermatozoa of CS-exposed fathers, while there were no significant differences in the count and morphological integrity of spermatozoa, as well as the proliferation of spermatogonia between CS- and RA-exposed fathers. Offspring from preconceptional CS-exposed mothers had lower body weights (p = 0.007). Moreover, data from offspring from CS-exposed fathers suggested a potential increase in body weight (p = 0.062). Conclusion We showed that preconceptional paternal CS exposure regulates spermatozoal miRNAs, and possibly influences the body weight of F1 progeny in early life. The regulated miRNAs may modulate transmittable epigenetic changes to offspring, thus influence the development of respiratory- and metabolic-related diseases such as obesity, a mechanism that warrants further studies for elaborate explanations.
Keywords: Metabolism; Genetics